Preparation method of ceramic reinforced aluminum-based composite wear-resistant coating, aluminum alloy material and train brake disc
By using laser cladding technology on the aluminum alloy brake disc substrate to form a wear-resistant coating of ceramic reinforced aluminum-based composite material, the problems of low hardness and poor wear resistance of aluminum alloy brake discs are solved, and efficient and economical wear-resistant coating preparation is achieved, which is suitable for the use of intercity train brake discs.
Patent Information
- Application Number
- CN202211229471.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-09
- Publication Date
- 2025-03-18
- Estimated Expiration
- 2042-10-09
AI Technical Summary
Due to the low hardness and poor wear resistance, existing aluminum alloy brake discs cannot be used directly as intercity train brake discs. The difficulty in processing is that pores are prone to occur during welding or cladding.
A ceramic reinforced aluminum-based composite wear-resistant coating is formed on the aluminum alloy matrix by laser cladding technology. A composite powder composed of titanium carbide powder and aluminum alloy powder is used. The titanium carbide powder accounts for 20 to 60% of the mass of the composite powder to improve the wear resistance and bonding strength of the coating.
A coating with high strength and good wear resistance is achieved on the surface of the aluminum alloy matrix, effectively enhancing the wear resistance of the aluminum alloy matrix, and is suitable for manufacturing intercity train brake discs, with simple processes and convenient implementation.
Smart Images

Figure CN116180071B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of coating preparation, and in particular to a method for preparing a ceramic-reinforced aluminum-based composite material wear-resistant coating, an aluminum alloy material and a train brake disc. Background Art
[0002] With the development of the rail transit industry, lightweighting has become a necessary step for upgrading rail transit equipment. Weight reduction can not only reduce traction consumption during train operation and save transportation costs, but also increase the speed of subways and reduce noise pollution. It also has an important impact on improving the stability and safety of train operation. As a basic braking device that plays a vital role in train driving safety, the reliability of the brake disc almost determines the reliability level of the entire basic braking device, which directly affects the driving safety of the train. Therefore, the research on lightweight brake discs has attracted more and more attention.
[0003] In view of this, this application is specially filed. Summary of the invention
[0004] The purpose of the present invention is to provide a method for preparing a ceramic reinforced aluminum-based composite material wear-resistant coating, an aluminum alloy material and a train brake disc.
[0005] The present invention is achieved in that:
[0006] In a first aspect, the present invention provides a method for preparing a ceramic reinforced aluminum-based composite material wear-resistant coating, comprising:
[0007] A ceramic reinforced aluminum-based composite material wear-resistant coating is formed on an aluminum alloy substrate by laser cladding. The raw material used for laser cladding is a composite powder composed of titanium carbide powder and aluminum alloy powder, and the titanium carbide powder accounts for 20-60% of the composite powder mass.
[0008] In an optional embodiment, the material of the aluminum alloy matrix is 2A70-T6 high-strength aluminum alloy, and the aluminum alloy powder is 2024 aluminum alloy powder.
[0009] In an optional embodiment, the parameters of laser cladding are: laser power: 2400~2800W, scanning speed: 150~250mm / min, shielding gas flow rate: 40~60L / min, spot diameter: 3~4mm, overlap rate: 40~60%, coaxial powder feeding method, powder feeding speed: 10~14g / min, carrier gas flow rate: 5~7L / min.
[0010] In an optional embodiment, the aluminum alloy substrate is pretreated before laser cladding is performed on the aluminum alloy substrate. The pretreatment method includes:
[0011] The aluminum alloy substrate is sandblasted to increase the roughness of the aluminum alloy substrate surface.
[0012] In an optional embodiment, the abrasive for sandblasting is brown corundum;
[0013] Preferably, the sandblasting pressure is 0.4-0.8 MPa;
[0014] Preferably, after sandblasting, the surface of the aluminum alloy substrate is cleaned with an ethanol solution.
[0015] In an optional embodiment, the preparation method of the composite powder is:
[0016] The titanium carbide powder and the aluminum alloy powder are placed in a ball mill and mixed thoroughly.
[0017] In an optional embodiment, the ball mill is a planetary ball mill, the ball milling speed is 140 to 180 r / min, and the ball milling time is 2.5 to 3.5 h;
[0018] Preferably, the small balls added to the ball mill are zirconium oxide balls with a diameter of 5 mm and 8 mm, and the total mass of the zirconium oxide balls is the same as the mass of the powder to be ball-milled;
[0019] Preferably, after ball milling, the obtained mixture is placed under vacuum conditions and dried at 100-140° C. for 1.5-2.5 h.
[0020] In an optional embodiment, the particle size of the composite powder is 50-150 μm.
[0021] In a second aspect, the present invention provides an aluminum alloy material, the surface of which is covered with a wear-resistant coating prepared by the preparation method of any of the aforementioned embodiments.
[0022] In a third aspect, the present invention provides a train brake disc, which is made of the aluminum alloy material as described in the aforementioned embodiment, or a wear-resistant coating is covered on the aluminum alloy brake disc substrate using the preparation method as described in any of the aforementioned embodiments.
[0023] The present invention has the following beneficial effects:
[0024] The preparation method provided by the present application can produce a coating with high strength and good wear resistance on the surface of an aluminum alloy substrate, which can effectively enhance the wear resistance of the surface of the aluminum alloy substrate, thereby improving its performance. The aluminum alloy material covered with the coating on the surface can be applied to the manufacture of intercity train brake discs, which can effectively meet the use requirements of intercity train brake discs. In addition, the preparation method of the coating provided by the present application also has the characteristics of not needing to preheat the substrate before preparing the coating, not needing to perform heat treatment after preparation, simple process, and easy implementation. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.
[0026] Figure 1 It is a schematic diagram of the laser cladding process of the present invention;
[0027] Figure 2 This is a photo of the aluminum alloy brake disc substrate used in the present invention;
[0028] Figure 3 Scanning electron microscope images of 2024 aluminum alloy powder and TiC powder used in Examples 1 to 5 of the present invention;
[0029] Figure 4 This is a cross-sectional macroscopic image of the coating prepared in Example 1 of the present invention;
[0030] Figure 5 This is a cross-sectional macroscopic image of the coating prepared in Example 2 of the present invention;
[0031] Figure 6 This is a cross-sectional macroscopic image of the coating prepared in Example 3 of the present invention. DETAILED DESCRIPTION
[0032] In order to make the purpose, technical scheme and advantages of the embodiments of the present invention clearer, the technical scheme in the embodiments of the present invention will be described clearly and completely below. If the specific conditions are not specified in the embodiments, they are carried out according to conventional conditions or conditions recommended by the manufacturer. If the manufacturer of the reagents or instruments used is not specified, they are all conventional products that can be purchased commercially.
[0033] In order to solve the problems mentioned in the background technology, the inventors consider that: currently, most of the brake disc materials of intercity trains are cast iron, and the weight of a single axle-mounted cast iron brake disc is about 76kg. If an aluminum alloy brake disc is used instead of a traditional cast iron brake disc, the weight of a single axle-mounted brake disc will drop to about 30kg, a decrease of more than 50%. At the same time, aluminum alloy has a higher thermal conductivity and heat capacity than cast iron, which can better deal with the thermal damage that is easily caused by the brake disc during service. However, the low hardness and poor wear resistance of aluminum alloy are its biggest disadvantages, which also lead to its inability to be used directly as a brake disc. Ceramic reinforced aluminum-based composite materials have the characteristics of low density and high wear resistance at the same time. Preparing a ceramic reinforced aluminum-based composite wear-resistant coating on the surface of an aluminum alloy brake disc is an efficient and economical method to improve its wear resistance. Therefore, using aluminum alloy as the matrix material, preparing a ceramic reinforced aluminum-based composite wear-resistant coating on its surface to increase the wear resistance of the material, so that the aluminum alloy material with a wear-resistant coating on the surface can be applied to the train brake disc has a certain feasibility. Therefore, after research, the inventors obtained the technical solution of this application.
[0034] The following is a detailed description of the preparation method of the ceramic reinforced aluminum-based composite wear-resistant coating, the aluminum alloy material and the train brake disc provided in the embodiments of the present application.
[0035] The method for preparing a ceramic reinforced aluminum-based composite material wear-resistant coating provided in an embodiment of the present application comprises:
[0036] like Figure 1 As shown, a ceramic reinforced aluminum-based composite wear-resistant coating is formed on an aluminum alloy substrate by laser cladding. The raw material used for laser cladding is a composite powder composed of titanium carbide powder and aluminum alloy powder, and the titanium carbide powder accounts for 20-60% of the mass of the composite powder.
[0037] Aluminum alloy powder and TiC powder are selected as cladding materials. TiC particles as a strengthening phase can effectively resist the indentation and plowing of the brake disc surface by the brake pad, greatly reducing the degree of abrasive wear and fatigue wear, thereby achieving the purpose of improving wear resistance. Aluminum alloy powder as a bonding phase has a higher bonding strength with the aluminum alloy matrix and is used to fix the TiC particles in the coating.
[0038] In the preparation process of the present application, aluminum alloy powder and TiC powder are used as coating materials, and laser cladding is used to form a coating on the surface of the aluminum alloy substrate. Compared with the plasma spraying method, the bonding strength of the coating is higher. The coating thickness formed by laser cladding can reach at least 2 mm, while the thickness of the plasma spraying coating can only reach 0.2 to 0.5 mm. If the coating thickness is increased further, the coating will easily fall off.
[0039] Since aluminum alloys are relatively active, pores are inevitable during welding or cladding, which is one of the difficulties in aluminum alloy processing. The present application utilizes the "stirring" effect of ceramic particles on the molten pool so that the gas can escape in time before the molten pool solidifies, thereby greatly reducing the number of pores in the coating. As the TiC content increases, the more significant the "stirring" effect is, the fewer the number of pores is. The above-mentioned "stirring" effect refers to the existence of convection in the molten pool with a higher temperature. The ceramic particles move under the action of convection, and the movement of the ceramic particles has a stirring effect, which can accelerate the discharge of bubbles.
[0040] Therefore, the preparation method provided by the present application can produce a coating with high strength and good wear resistance on the surface of the aluminum alloy substrate, which can effectively enhance the wear resistance of the surface of the aluminum alloy substrate, thereby improving its performance. The aluminum alloy material covered with the coating on the surface can be used to manufacture intercity train brake discs, which can effectively meet the use requirements of intercity train brake discs. In addition, the preparation method of the coating provided by the present application also has the characteristics of not needing to preheat the substrate before preparing the coating, not needing to perform heat treatment after preparation, simple process, and easy implementation.
[0041] Preferably, the material of the aluminum alloy matrix is 2A70-T6 high-strength aluminum alloy, and its specific composition is: the composition by mass percentage is Mn: 0.2%, Cu: 1.9-2.5%, Mg: 1.4-1.8%, Si: 0.35%, Fe: 0.9-1.5%, Ni: 0.9-1.5%, and the balance is Al and inevitable trace impurities. The aluminum alloy powder is 2024 aluminum alloy powder.
[0042] 2A70-T6 high-strength aluminum alloy has high strength. It and 2024 aluminum alloy are both 2 series aluminum alloys. The two have similar compositions, good coating compatibility, and better bonding strength. The ceramic reinforced aluminum-based composite material wear-resistant coating made on the surface of 2A70-T6 high-strength aluminum alloy matrix material will make the material have the characteristics of light weight, high strength and good wear resistance. 2A70-T6 high-strength aluminum alloy brake disc matrix such as Figure 2 shown.
[0043] Preferably, the particle size of the composite powder is 50-150 μm.
[0044] If the particle size is too small, the powder fluidity will be poor during laser cladding, which may easily cause powder blockage, uneven powder discharge, powder burnout, etc. If the particle size is too large, the two powders are not easy to mix evenly, and the powder may not be fully melted during the cladding process and may block the powder outlet. Therefore, the appropriate particle size of laser cladding powder is selected to be 50-150 microns.
[0045] Specifically, the preparation method of the ceramic reinforced aluminum-based composite material wear-resistant coating is:
[0046] S1. Matrix pretreatment
[0047] Specifically:
[0048] First, use an angle grinder to grind the surface of the substrate smooth and remove the oxide film and oil stains on the surface;
[0049] Then, the substrate surface is sandblasted to increase its surface roughness to reduce the reflection of the laser. The abrasive is brown corundum, and the sandblasting pressure is 0.4-0.8 MPa (for example, 0.4 MPa, 0.6 MPa or 0.8 MPa).
[0050] Finally, the sandblasted substrate was cleaned with an ethanol solution.
[0051] S2. Preparation of composite powder
[0052] The titanium carbide powder and the 2024 aluminum alloy powder are placed in a ball mill and fully mixed according to the titanium carbide powder accounting for 20 to 60% of the mass of the composite powder.
[0053] Preferably, the ball mill is a planetary ball mill, the ball milling speed is 140-180 r / min (e.g., 140 r / min, 160 r / min, or 180 r / min), and the ball milling time is 2.5-3.5 h (e.g., 2.5 h, 3 h, or 3.5 h). Further, the small balls added to the high-energy ball milling tank of the ball mill are zirconia small balls with diameters of 5 mm and 8 mm, and the total mass of the zirconia small balls is the same as the mass of the powder to be ball milled.
[0054] The above ball milling conditions can ensure that the powder is fully mixed and uniformly obtained.
[0055] Preferably, after ball milling, the obtained mixture is placed under vacuum conditions and dried at 100-140° C. (eg, 100° C., 120° C. or 140° C.) for 1.5-2.5 h (eg, 1.5 h, 2 h or 2.5 h).
[0056] The ball-milled mixture is fully dried to remove moisture brought to the powder by gaseous water in the air, thereby ensuring a coating with better performance.
[0057] Preferably, experiments have found that when the TiC content accounts for about 40% of the coating mass, the coating has better wear resistance. Therefore, the best ratio is that TiC powder accounts for 35-45% of the composite powder mass.
[0058] S3. Preparation of coating
[0059] First, the pretreated aluminum alloy substrate is fixed on the stage using a clamp;
[0060] Then, if Figure 1 As shown, laser cladding is performed, and the process parameters are:
[0061] Laser power: 2400-2800W (e.g. 2400W, 2600W or 2800W), scanning speed: 150-250mm / min (e.g. 150mm / min, 200mm / min or 250mm / min), shielding gas flow rate: 40-60L / min (e.g. 40L / min, 50L / min or 60L / min), spot diameter: 3-4mm (e.g. 3mm, 3.5mm or 4mm), overlap rate: 40-60% (e.g. 40%, 50% or 60%), coaxial powder feeding method, powder feeding speed: 10-14g / min (e.g. 10g / min, 12g / min or 14g / min), carrier gas flow rate: 5-7L / min (e.g. 5L / min, 6L / min or 7L / min).
[0062] Preferably, in order to ensure better performance, the process parameters of laser cladding are:
[0063] Laser power: 2500-2700W (for example, 2500W, 2600W or 2700W), scanning speed: 150-250mm / min (for example, 180mm / min, 200mm / min or 220mm / min), shielding gas flow rate: 45-55L / min (for example, 45L / min, 50L / min or 55L / min), spot diameter: 3-4mm (for example, 3mm, 3.5mm or 4mm), overlap rate: 45-55% (for example, 45%, 50% or 55%), coaxial powder feeding method, powder feeding speed: 11-13g / min (for example, 11g / min, 12g / min or 13g / min), carrier gas flow rate: 5-7L / min (for example, 5L / min, 6L / min or 7L / min).
[0064] The aluminum alloy material provided in the embodiment of the present application has its surface covered with a wear-resistant coating prepared by the preparation method provided in the embodiment of the present application.
[0065] Since the aluminum alloy material is covered with a ceramic-reinforced aluminum-based composite material wear-resistant coating on its surface through the preparation method provided in the embodiment of the present application, the aluminum alloy material has the characteristics of high strength and good wear resistance.
[0066] The train brake disc provided in the embodiment of the present application is made of the aluminum alloy material provided in the embodiment of the present application, or a wear-resistant coating is covered on the aluminum alloy brake disc substrate using the preparation method provided in the embodiment of the present application.
[0067] Since the surface of the train brake disc is covered with a ceramic-reinforced aluminum-based composite material wear-resistant coating, it has the characteristics of light weight, high strength and good wear resistance.
[0068] The features and performance of the present invention are further described in detail below in conjunction with the embodiments.
[0069] Example 1
[0070] This embodiment provides a method for forming a coating on the surface of a 2A70-T6 high-strength aluminum alloy brake disc substrate. A coating of about 2 mm is prepared on the substrate surface. The contents of this embodiment are described with reference to the above.
[0071] The steps for cladding material selection and preparation are as follows:
[0072] Select commercial 2024 aluminum alloy powder with a purity of not less than 99.9% and TiC powder as cladding materials, with a powder particle size of 50-150μm;
[0073] The two powders were weighed in a mass ratio of 2024 aluminum alloy: TiC = 4:1 using an electronic scale with an accuracy of 0.1 mg and placed in a stainless steel high-energy ball mill;
[0074] In order to make the powders mix evenly, zirconia balls with diameters of 5 mm and 8 mm were added to the stainless steel tank, respectively. The mass of the balls was the same as that of the powders. After vacuuming, the stainless steel tank was placed in a planetary ball mill and mixed for 3 h at a speed of 160 r / min.
[0075] The mixed powder was taken out and placed in a vacuum drying oven at 120°C for 2 hours to remove moisture from the powder. Finally, the powder was taken out and sealed for storage.
[0076] The substrate pretreatment process steps are as follows:
[0077] Use an angle grinder to smooth the surface of the substrate and remove the oxide film and oil stains on the surface;
[0078] The surface is sandblasted to improve its surface roughness to reduce the reflection of laser. The abrasive is brown corundum and the sandblasting pressure is 0.6MPa;
[0079] Clean the substrate surface with ethanol.
[0080] The coating preparation process steps are as follows:
[0081] Fix the brake disc substrate on the stage using a clamp;
[0082] Adjust the cladding process: laser power: 2600W, scanning speed: 200mm / min, shielding gas flow: 50L / min, spot diameter: 3.5mm, overlap rate: 50%, coaxial powder feeding method, powder feeding speed: 12g / min, carrier gas flow: 6L / min.
[0083] Example 2
[0084] This embodiment provides a method for forming a coating on the surface of a 2A70-T6 high-strength aluminum alloy brake disc substrate. A coating of about 2 mm is prepared on the substrate surface. The contents of this embodiment are described with reference to the above.
[0085] The cladding material selection and preparation process steps are as follows:
[0086] Select commercial 2024 aluminum alloy powder with a purity of not less than 99.9% and TiC powder as cladding materials, with a powder particle size of 50-150μm;
[0087] The two powders were weighed in a mass ratio of 2024 aluminum alloy: TiC = 3:2 using an electronic scale with an accuracy of 0.1 mg and placed in a stainless steel high-energy ball mill;
[0088] In order to make the powders mix evenly, zirconia balls with diameters of 5 mm and 8 mm were added to the stainless steel tank, respectively. The mass of the balls was the same as that of the powders. After vacuuming, the stainless steel tank was placed in a planetary ball mill and mixed for 3 h at a speed of 160 r / min.
[0089] The mixed powder was taken out and placed in a vacuum drying oven at 120°C for 2 hours to remove moisture from the powder. Finally, the powder was taken out and sealed for storage.
[0090] The substrate pretreatment process steps and coating preparation process steps are the same as those in Example 1.
[0091] Example 3
[0092] This embodiment provides a method for forming a coating on the surface of a 2A70-T6 high-strength aluminum alloy brake disc substrate. A coating of about 2 mm is prepared on the substrate surface. The contents of this embodiment are described with reference to the above.
[0093] The steps for cladding material selection and preparation are as follows:
[0094] Select commercial 2024 aluminum alloy powder with a purity of not less than 99.9% and TiC powder as cladding materials, with a powder particle size of 50-150μm;
[0095] The two powders were weighed in a mass ratio of 2024 aluminum alloy: TiC = 2:3 using an electronic scale with an accuracy of 0.1 mg and placed in a stainless steel high-energy ball mill;
[0096] In order to make the powders mix evenly, zirconia balls with diameters of 5 mm and 8 mm were added to the stainless steel tank, respectively. The mass of the balls was the same as that of the powders. After vacuuming, the stainless steel tank was placed in a planetary ball mill and mixed for 3 h at a speed of 160 r / min.
[0097] The mixed powder was taken out and placed in a vacuum drying oven at 120°C for 2 hours to remove moisture from the powder. Finally, the powder was taken out and sealed for storage.
[0098] The substrate pretreatment process steps and coating preparation process steps are the same as those in Example 1.
[0099] Example 4
[0100] This embodiment is basically the same as the embodiment 2, except that the process parameters of laser melting are different:
[0101] Laser power: 2400W, scanning speed: 150mm / min, shielding gas flow rate: 40L / min, spot diameter: 3mm, overlap rate: 40%, coaxial powder feeding method, powder feeding speed: 10g / min, carrier gas flow rate: 5L / min.
[0102] Example 5
[0103] This embodiment is basically the same as the embodiment 2, except that the process parameters of laser melting are different:
[0104] Laser power: 2800W, scanning speed: 250mm / min, shielding gas flow rate: 60L / min, spot diameter: 4mm, overlap rate: 60%, coaxial powder feeding method, powder feeding speed: 14g / min, carrier gas flow rate: 7L / min.
[0105] Example 6
[0106] This embodiment is basically the same as Embodiment 2, except that the 2024 aluminum alloy powder in Embodiment 2 is replaced by 7075 aluminum alloy powder.
[0107] Comparative Example 1
[0108] The comparative example is a 2A70 aluminum alloy substrate, the surface of which is polished to remove the oxide film, and no other treatment is performed.
[0109] Comparative Example 2
[0110] This comparative example is basically the same as Example 2, except that the coating is formed by plasma spraying. The plasma spraying parameters are plasma spraying parameters; current: 380A, voltage: 40V, spraying distance: 150mm, argon flow rate: 80L / min, hydrogen flow rate: 10L / min, powder feeding amount: 18g / min. The coating with a thickness of about 2mm is obtained by spraying.
[0111] Comparative Example 3
[0112] This comparative example is basically the same as Example 2, except that: 2024 aluminum alloy: TiC = 1:4.
[0113] Comparative Example 4
[0114] This comparative example is basically the same as Example 2, except that: 2024 aluminum alloy: TiC = 4.5:0.5.
[0115] Comparative Example 5
[0116] The WC / Ni-based coating was prepared on the surface of 7075-T6 aluminum alloy brake disc by plasma spraying, and the coating thickness was 0.5 mm.
[0117] Comparative Example 6
[0118] This comparative example is substantially the same as Example 2, except that the coating does not contain titanium carbide.
[0119] Experimental Example 1
[0120] The images of 2024 aluminum alloy powder and TiC powder observed by scanning electron microscope are as follows Figure 3 As shown in the figure, the sphericity of 2024 aluminum alloy powder is good, while the TiC powder is irregular in shape. Figures 4 to 6 The cross-sectional macroscopic images of the coatings prepared in Examples 1 to 3 show that the coatings are well formed, have a smooth surface and a small surface roughness. At the same time, it can be clearly seen that the coating and the substrate are metallurgically bonded, and there are no defects such as cracks and unfused areas in the bonding area. The coating prepared in Example 2 has a small porosity and the TiC particles are evenly distributed. Since aluminum alloys are relatively active, pores are inevitable during welding or cladding, which is one of the difficulties in aluminum alloy processing. However, the technical solution of the present application utilizes the "stirring" effect of ceramic particles on the molten pool, allowing the gas to escape in time before the molten pool solidifies, thereby greatly reducing the number of pores in the coating. As the TiC content increases, the "stirring" effect becomes more significant and the number of pores decreases.
[0121] The coating thicknesses of Examples 1 to 3 are all about 2 mm, while the WC / Ni-based coating prepared on the surface of a 7075T6 aluminum alloy brake disc by plasma spraying generally has a thickness of 0.2 to 0.5 mm. The coating thickness of the former is 4 to 10 times that of the latter, and thus has a better protective effect on the substrate.
[0122] Experimental Example 2
[0123] The hardness of the test pieces of Examples 1 to 6 and Comparative Examples 2 to 6 was measured by a Bush hardness tester, and a micro shear test was performed on them using a micro shear device to test their shear strength, and the tensile strength and elongation were indirectly obtained. The results are shown in Table 1.
[0124] Table 1
[0125]
[0126] It can be seen from the above experimental data that as the TiC particle content increases, the hardness of the coating increases, which is due to the dispersion strengthening effect of the TiC ceramic strengthening phase. At the same time, due to the fewer pores and uniform distribution of TiC in Example 2, the tensile strength of the coating and the bonding strength with the substrate are the highest. However, the bonding strength of the WC / Ni-based coating (Comparative Example 5) prepared on the surface of the 7075T6 aluminum alloy brake disc by plasma spraying is generally 80-83MPa, and the bonding strength of the coatings of Examples 1-6 is about 3.6 times that of the WC / Ni-based coating (Comparative Example 5). At the same time, as the TiC content increases, its hindering effect on the plastic deformation of the Al matrix is greater, so the cross-sectional shrinkage of the coating continues to decrease. Comparing the coatings of Examples 1-6 with the Al2O3 / 2024 coating prepared by thermal spraying, the elongation of the latter is about 5%, and the elongation of the coatings of Examples 1-6 is increased by 2-4 times.
[0127] Comparing Example 4 and Example 5 with Example 2, the various properties of Example 2 are significantly higher than those of Example 4 and Example 5, indicating that the best effect is achieved when the laser process parameters are in Example 2, indicating that the process parameters of laser cladding have a greater impact on the performance of the cladding layer, among which the laser power and scanning speed are particularly important. The greater the laser power, the more the amount of melted cladding metal, the greater the probability of generating pores, the temperature of the substrate surface will also increase accordingly, and the deformation and cracking phenomena will increase; when the laser power is small, there may be a problem that only the cladding powder is melted and the substrate is not melted. At this time, the surface of the cladding layer shows local pilling, voids, etc., and the purpose of complete surface cladding may not be achieved. The scanning speed has a similar effect to the laser power. If the scanning speed is too high, the alloy powder may not be completely melted, the cladding effect cannot be achieved, and the powder utilization rate is low; if the scanning speed is too low, the molten pool exists for a long time, the powder is overburned, the alloy element is lost, and the heat input of the substrate is large, which will increase the deformation. But even so, although the effects of Example 4 and Example 5 are worse than those of Example 2, they still have significantly better effects compared with each comparative example.
[0128] Comparing Example 2 with Example 6, the bonding strength of the coating in Example 2 is significantly higher than that in Example 6, indicating that the aluminum alloy powder of the same series as the substrate can be better bonded to the substrate than other series of aluminum alloy powders.
[0129] Comparing Example 2 with Comparative Example 2, since the coating thickness exceeds the common thickness of the coating prepared by plasma spraying and there are more microcracks in the coating, the tensile strength and elongation of the coating are lower than those of Examples 1 to 3. In particular, the bonding strength between the coating and the substrate in Comparative Example 2 is only 70.2 MPa. This shows that laser cladding technology is more applicable in this solution.
[0130] Comparing Example 2 with Comparative Example 3, it is found that Comparative Example 3 cannot obtain a well-formed coating, indicating that the aluminum alloy content in the composite powder should not be too much, and too much TiC content will lead to difficulty in coating formation. Comparing Example 2 with Comparative Example 4, the hardness and tensile strength of Example 2 are significantly better than those of Comparative Example 4, indicating that the TiC content in the composite powder should not be too little, and too little TiC content will not have a significant strengthening effect on the coating and cannot meet the use requirements. This shows that the ratio of 2024 aluminum alloy to titanium carbide in the composite powder should be within an appropriate range, and a coating with excellent performance cannot be obtained if it exceeds the range required by this application.
[0131] Comparing Example 2 with Comparative Example 5, the bonding strength between the coating and the substrate of Example 2 is significantly higher than that of Comparative Example 5, which is 3.6 times that of Comparative Example 5, which once again shows that plasma spraying technology is not applicable in this application.
[0132] Comparing Example 2 with Comparative Example 6, except for the elongation, the mechanical properties of Comparative Example 6 are relatively poor, indicating that the addition of TiC is the main reason for the strengthening of the coating.
[0133] Experimental Example 3
[0134] Friction and wear tests were carried out on Examples 1 to 6 and Comparative Examples 1 to 6 at four temperatures: room temperature, 100° C., 200° C., and 300° C. The wear rates are shown in Table 2.
[0135] Table 2
[0136]
[0137] It can be seen from the above table that the coatings prepared by the methods provided in Examples 1-5 of the present application all have good wear resistance and are sufficient to meet the use requirements of train brake discs. In particular, the coating prepared in Example 2 shows the lowest wear rate at all temperatures and has the best wear resistance, which can fully meet the wear resistance requirements of brake discs.
[0138] Comparing Example 2 with Example 6, the wear resistance of Example 2 is significantly better than that of Example 6, indicating that a coating with better wear resistance can be obtained by using 2020 aluminum alloy as a bonding phase compared with other aluminum alloys.
[0139] Comparing Example 2 with Comparative Example 2, the wear resistance of the coating of the same thickness prepared by plasma spraying is significantly worse, indicating that only the coating prepared by laser cladding in the present application can ensure better performance.
[0140] Comparing Example 2 with Comparative Example 3 and Comparative Example 4, the wear resistance of Example 2 is significantly better than that of Comparative Example 3 and Comparative Example 4, indicating that too much or too little aluminum alloy in the composite powder will lead to poor wear resistance. This shows that the ratio of 2024 aluminum alloy to titanium carbide in the composite powder should be within a suitable range, and a coating with excellent performance cannot be obtained if it exceeds the range required by this application.
[0141] Comparing Example 2 with Comparative Example 6, the wear resistance of Example 2 is significantly better than that of Comparative Example 6, indicating that TiC is the main reason for the improved wear resistance of the coating.
[0142] In summary, the preparation method of the ceramic reinforced aluminum-based composite wear-resistant coating, aluminum alloy material or train brake disc provided in the present application has the following advantages:
[0143] 1. 2A70 aluminum alloy is selected as the brake disc substrate, and the cladding material is 2024 aluminum alloy. Both are 2 series aluminum alloys with similar composition, so the compatibility between the coating and the substrate is better than other systems, and there is no problem of interface corrosion between heterogeneous materials. At the same time, the density of TiC and 2024 aluminum alloy powder is close, so the lightweight effect is significant.
[0144] 2. Compared with other surface treatment technologies such as thermal spraying, laser cladding technology can make the coating and the substrate metallurgically bonded, so the bonding strength is higher.
[0145] 3. Compared with the brake disc substrate, the wear resistance of the coating is greatly improved, which is enough to meet the wear resistance requirements of the brake disc.
[0146] 4. There is no need to preheat the substrate before preparing the coating, and no post-heat treatment is required after preparation. Therefore, the process is simple and easy to implement. At the same time, since the linear expansion coefficient of the cladding material is similar to that of the brake disc substrate, the coating will not have crack defects.
[0147] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A train brake disc, characterized in that: It includes an aluminum alloy substrate and a wear-resistant coating covered on the aluminum alloy substrate. The preparation method of the wear-resistant coating includes: A ceramic-reinforced aluminum-based composite material wear-resistant coating is formed on an aluminum alloy substrate by laser cladding, wherein the raw material used for laser cladding is a composite powder composed of titanium carbide powder and aluminum alloy powder, wherein the titanium carbide powder accounts for 60% of the mass of the composite powder; The material of the aluminum alloy substrate is 2A70-T6 high-strength aluminum alloy; The aluminum alloy powder is 2024 aluminum alloy powder.
2. The train brake disc according to claim 1, characterized in that: The parameters of laser cladding are: laser power: 2400~2800W, scanning speed: 150~250mm / min, shielding gas flow: 40~60L / min, spot diameter: 3~4mm, overlap rate: 40~60%, coaxial powder feeding method, powder feeding speed: 10~14g / min, carrier gas flow: 5~7L / min.
3. The train brake disc according to claim 1, characterized in that: Before laser cladding is performed on the aluminum alloy substrate, the aluminum alloy substrate is pretreated, and the pretreatment method includes: The aluminum alloy substrate is sandblasted to increase the roughness of the surface of the aluminum alloy substrate.
4. The train brake disc according to claim 3, characterized in that: The abrasive used for sandblasting is brown corundum.
5. The train brake disc according to claim 4, characterized in that: The sandblasting pressure is 0.4~0.8MPa.
6. The train brake disc according to claim 4, characterized in that: After sandblasting, the surface of the aluminum alloy substrate is cleaned with an ethanol solution.
7. The train brake disc according to claim 1, characterized in that: The preparation method of the composite powder is: The titanium carbide powder and the aluminum alloy powder are placed in a ball mill and mixed thoroughly.
8. The train brake disc according to claim 7, characterized in that: The ball mill is a planetary ball mill, the ball milling speed is 140~180 r / min, and the ball milling time is 2.5~3.5h.
9. The train brake disc according to claim 7, characterized in that: The small balls added into the ball mill are zirconium oxide small balls with diameters of 5 mm and 8 mm, and the total mass of the zirconium oxide small balls is the same as the mass of the powder to be ball-milled.
10. The train brake disc according to claim 7, characterized in that: After ball milling, the obtained mixture was placed under vacuum conditions and dried at 100-140°C for 1.5-2.5h.
11. The train brake disc according to claim 1, characterized in that: The particle size of the composite powder is 50-150 μm.
Citation Information
Patent Citations
Material for preparing bullet train brake pad and preparing method thereof
CN102537157A